Step * 1 of Lemma bag-summation-equal-implies-all-equal


1. [T] Type
2. [b] bag(T)
3. [f] {x:T| x ↓∈ b}  ⟶ ℤ
4. [g] {x:T| x ↓∈ b}  ⟶ ℤ
5. (∀x:{x:T| x ↓∈ b} (x ↓∈  (f[x] g[x] ∈ ℤ))) supposing 
      ((Σ(x∈b). g[x] ≤ Σ(x∈b). f[x]) and 
      (∀x:{x:T| x ↓∈ b} (x ↓∈  (f[x] ≤ g[x]))))
⊢ (∀x:T. (x ↓∈  (f[x] g[x] ∈ ℤ))) supposing ((Σ(x∈b). g[x] ≤ Σ(x∈b). f[x]) and (∀x:T. (x ↓∈  (f[x] ≤ g[x]))))
BY
TACTIC:RepeatFor (Intro) }

1
1. [T] Type
2. [b] bag(T)
3. [f] {x:T| x ↓∈ b}  ⟶ ℤ
4. [g] {x:T| x ↓∈ b}  ⟶ ℤ
5. (∀x:{x:T| x ↓∈ b} (x ↓∈  (f[x] g[x] ∈ ℤ))) supposing 
      ((Σ(x∈b). g[x] ≤ Σ(x∈b). f[x]) and 
      (∀x:{x:T| x ↓∈ b} (x ↓∈  (f[x] ≤ g[x]))))
6. [%] : ∀x:T. (x ↓∈  (f[x] ≤ g[x]))
7. [%3] : Σ(x∈b). g[x] ≤ Σ(x∈b). f[x]
⊢ ∀x:T. (x ↓∈  (f[x] g[x] ∈ ℤ))

2
1. Type
2. bag(T)
3. {x:T| x ↓∈ b}  ⟶ ℤ
4. {x:T| x ↓∈ b}  ⟶ ℤ
5. (∀x:{x:T| x ↓∈ b} (x ↓∈  (f[x] g[x] ∈ ℤ))) supposing 
      ((Σ(x∈b). g[x] ≤ Σ(x∈b). f[x]) and 
      (∀x:{x:T| x ↓∈ b} (x ↓∈  (f[x] ≤ g[x]))))
6. ∀x:T. (x ↓∈  (f[x] ≤ g[x]))
⊢ istype(Σ(x∈b). g[x] ≤ Σ(x∈b). f[x])


Latex:


Latex:

1.  [T]  :  Type
2.  [b]  :  bag(T)
3.  [f]  :  \{x:T|  x  \mdownarrow{}\mmember{}  b\}    {}\mrightarrow{}  \mBbbZ{}
4.  [g]  :  \{x:T|  x  \mdownarrow{}\mmember{}  b\}    {}\mrightarrow{}  \mBbbZ{}
5.  (\mforall{}x:\{x:T|  x  \mdownarrow{}\mmember{}  b\}  .  (x  \mdownarrow{}\mmember{}  b  {}\mRightarrow{}  (f[x]  =  g[x])))  supposing 
            ((\mSigma{}(x\mmember{}b).  g[x]  \mleq{}  \mSigma{}(x\mmember{}b).  f[x])  and 
            (\mforall{}x:\{x:T|  x  \mdownarrow{}\mmember{}  b\}  .  (x  \mdownarrow{}\mmember{}  b  {}\mRightarrow{}  (f[x]  \mleq{}  g[x]))))
\mvdash{}  (\mforall{}x:T.  (x  \mdownarrow{}\mmember{}  b  {}\mRightarrow{}  (f[x]  =  g[x])))  supposing 
          ((\mSigma{}(x\mmember{}b).  g[x]  \mleq{}  \mSigma{}(x\mmember{}b).  f[x])  and 
          (\mforall{}x:T.  (x  \mdownarrow{}\mmember{}  b  {}\mRightarrow{}  (f[x]  \mleq{}  g[x]))))


By


Latex:
TACTIC:RepeatFor  2  (Intro)




Home Index